Effect of Operrationg Cash Flows on the Amount of Dividends Dividends towards the Company - Galih Satrio Putra Prili (Journal of Contemporary Information Technology, Management, and Accounting, 2021)
Every company that is listed on the Indonesia Stock Exchange (IDX) must have a different dividend policy as a return on funds provided by investors. This dividend policy includes distributing dividends distributing dividends or holding it for the progress of the company itself. The dividends that will be distributed later can be a benchmark for the company whether invesors are interested or not. This operating cash flow is used as an independent variable and for the dependent variable, dividends are distributed for the period. The population in this study were 20 companies that were on the IDX from 4 kinds of sectors, namely food, bangking, mining and also medicine. The method use later is descriptive statistical testing, classical assumption test and t test and f test. From the test results that have been tested, it is found that the operating cash flow has a significant effect on the company’s dividend distribution.